STRATEGI REKRUTMEN DAN SELEKSI PENDIDIK DALAM MENGINTEGRASIKAN KOMPETENSI AKADEMIK DAN KEAGAMAAN DI SMP SAINS QUR’AN BUSTANUL FALAH GENTENG BANYUWANGI - Imam Wahyono; Moh. Hamzah; Kholilur Rahman; Bunga Citra Lestari (International Conference on Humanity Education and Society (ICHES), 2025)
This study examines the recruitment and selection strategies for educators at SMP Sains Qur'an Bustanul Falah Genteng Banyuwangi, designed to integrate academic and religious competencies in a balanced manner. The background of this research is based on a key issue faced by Islamic educational institutions: the dilemma in selecting educators who excel in either academic or religious aspects due to the absence of standardized assessment systems to measure both simultaneously. This study aims to describe the strategies, criteria, and selection mechanisms for educators at SMP Sains Qur'an Bustanul Falah, as well as identify the challenges faced in its implementation. A descriptive qualitative approach was used, with data collected through observations, in-depth interviews, and documentation involving the school principal, foundation supervisors, and the selection committee. Data analysis employed reduction, data display, and conclusion drawing, along with source triangulation to validate findings. The results show that the selection strategy emphasizes integration between academic competencies (minimum bachelor's degree, pedagogical skills, classroom management) and religious competencies (Qur'an memorization skills, understanding of Ahlussunnah wal Jama’ah An-Nahdliyah). The selection mechanism includes administrative selection, academic competency tests, Qur'anic recitation proficiency exams, and interviews on NU ideology. The main challenges identified are the limited availability of candidates with both competencies and the absence of standardized assessment indicators for religious competencies. This study recommends the development of systematic assessment standards for religious competencies as a solution to strengthen the recruitment process in Islamic educational institutions.